K slovenskim diplomatskim študijam - Brglez, Milan (Teorija in praksa, 2011)
The article introduces a special issue of Teorija in praksa providing a comparative state of the art of Foreign Policy Analysis and Diplomatic Studies in international as well as Slovenian perspectives. Its main argument is that an academic gap between Slovenian and international developments are narrower that the one, celebrated this year as the twenty years of Slovenia's statehood. While the developments of Slovenian Foreign Policy Analysis are comparable with world's trends, one may hope that the similar developments will be undertaken also in Slovenian Diplomatic Studies. Those are understood as an interdisciplinary field confronting scientific and practical discourses on diplomacy, primarily conceived both, as a constitutive institution of international community and as a mean of foreign policy.
Keywords: Foreign policy; Zunanja politika; Diplomacija; Diplomacy; Slovenia; Slovenija; diplomatske študije